Improving The Methodology Of Teaching Essay Creation In Uzbek Language Classes (Progress Annals: Journal of Progressive Research, 2024)
This article aims to study the problems encountered in teaching essay writing, to propose innovative methodologies to overcome these difficulties, and to emphasize the importance of developing creativity and critical thinking in the process of creating an essay in Uzbek language classes. By adopting new approaches and fostering a culture of creativity and expression, teachers can make the teaching of essay writing a dynamic and enriching learning experience for students